Total laparoscopic hysterectomy versus da Vinci robotic hysterectomy: is using the robot beneficial? - Soto, Enrique (Korean Society of Gynecologic Oncology and Colposcopy, 2011)
OBJECTIVE: To compare the outcomes of total laparoscopic to robotic approach for hysterectomy and all indicated procedures after controlling for surgeon and other confounding factors. METHODS: Retrospective chart review of all consecutive cases of total laparoscopic and da Vinci robotic hysterectomies between August 2007 and July 2009 by two gynecologic oncology surgeons. Our primary outcome measure was operative procedure time. Secondary measures included complications, conversion to laparotomy, estimated blood loss and length of hospital stay. A mixed model with a random intercept was applied to control for surgeon and other confounders. Wilcoxon rank-sum, chi-square and Fisher's exact tests were used for the statistical analysis. RESULTS: The 124 patients included in the study consisted of 77 total laparoscopic hysterectomies and 47 robotic hysterectomies. Both groups had similar baseline characteristics, indications for surgery and additional procedures performed. The difference between the mean operative procedure time for the total laparoscopic hysterectomy group (111.4 minutes) and the robotic hysterectomy group (150.8 minutes) was statistically significant (p=0.0001) despite the fact that the specimens obtained in the total laparoscopic hysterectomy group were significantly larger (125 g vs. 94 g, p=0.002). The robotic hysterectomy group had statistically less estimated blood loss than the total laparoscopic hysterectomy group (131.5 mL vs. 207.7 mL, p=0.0105) however no patients required a blood transfusion in either group. Both groups had a comparable rate of conversion to laparotomy, intraoperative complications, and length of hospital stay. CONCLUSION: Total laparoscopic hysterectomy can be performed safely and in less operative time compared to robotic hysterectomy when performed by trained surgeons.